The effect of fused deposition modeling parameters (FDM) on the mechanical properties of polylactic acid (PLA) printed parts - Ahmad, Mohd Nazri; Ishak, Mohamad Ridzwan; Zulkafle Hannah, Muhammad Zulfikri (Semarak Ilmu Publishing, 2024)
The most common method for additive manufacturing of thermoplastics is fused deposition modeling (FDM), which is becoming a growing trend in a variety of engineering applications since it can easily create intricate parts. The appropriate choice of process parameters has a significant impact on the mechanical qualities of 3D-printed parts. This study examined the effect of four crucial process variables on the tensile strength of polylactic acid (PLA) samples: infill density, printing speed, build orientation, and layer thickness. Samples were printed in accordance with ASTM D638 using an FDM 3D printer. The findings of this study show that the tensile strength of the PLA-printed samples is highly influenced by factors such as layer thickness, build orientation, and infill density. The PLA-printed samples' tensile strength and Young's modulus were significantly affected by the 90° orientations, hollow infill, 0.4 mm thickness, and 100 mm/s speed. Therefore, as the FDM 3D printer becomes progressively more significant for manufacturing engineering components, finding the parameter values that may lead to stronger mechanical and physical characteristics would definitely help designers and manufacturers globally.